Peran Sektor Pertanian terhadap Pertumbuhan Ekonomi di Kota Denpasar - QIPTIAH, AINI MARYATUL; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.1, November 2024, 2024)
The Role of Agricultural Sector to Economic Growth in Denpasar City. The agricultural sector still contributes to the Gross Regional Domestic Product (GRDP) in the City of Denpasar even though the condition of the rapid conversion of land functions indicates that efforts are needed to develop the role of the agricultural sector in the City of Denpasar. This study aims to determine the position of the agricultural sector in Denpasar City, explain the leading and non-leading sectors, repositioning the sector in the future, and sector competitiveness. This study uses the Klassen Typology method, Location Quotient (LQ) method, the Dynamic Location Quotient (DLQ) method, and the shift share method. The results of the study show that the position of the agricultural sector in Denpasar City is a sector that is relatively underdeveloped. Denpasar City has 12 leading sectors and 5 non-leading sectors, one of which is the agricultural sector. There are 4 prospective sectors and 13 non-prospective sectors, one of which is the agricultural sector. The agricultural sector is a competitive sector. Advice that can be given to the Denpasar City government is that it is expected to continue to innovate on agricultural productivity in Denpasar City with increasingly narrow land, maintain agricultural commodity production, improve facilities or incentives for lagging sectors.